Quality Control Analysis of Linear Accelerator Radiotherapy Device in the Department of Radiotherapy at Pasar Minggu District Hospital - Apriantoro, Nursama Heru; Wulandari, Ira; Sari, Gando; Riyangga, Dea; Murdaka, Egi Kamal; Wellyam, Petra Pratama; Kurnia, Try Wulan; Fathoni, Imam Muhamad (Jurusan Fisika FMIPA Universitas Andalas, 2024)
Radiation accidents pose a significant risk, often stemming from inadequate calibration of radiation output, procedural lapses, and faults in radiation monitoring systems. Addressing these risks is pivotal, particularly in radiotherapy, where the precise functioning of linear accelerator (Linac) devices is crucial. This study delves into the quality control procedures applied to the Linac radiotherapy device within the Department of Radiotherapy at Pasar Minggu District Hospital. Drawing upon the renowned reference standards set by the AAPM Task Group 142 and BAPETEN Regulation No. K2N.2/MT-08, this research, conducted in November 2022, rigorously evaluated the mechanical, dosimetry, and safety aspects of the Linac device. The examination encompassed critical elements, including gantry angles, optical distance indicators, laser precision, collimator angles, light field size, and photon and electron beam outputs. Safety features such as door interlocks, audiovisual indicators, and radiation alert systems were scrutinized. The analysis reveals a reassuring finding: the Linac device at Pasar Minggu District Hospital adheres commendably to tolerance limits specified by reference standards across all measured parameters, indicating robust performance in mechanics, dosimetry, and safety. This meticulous quality control regimen has proven highly effective in ensuring the device's operational integrity and safety, affirming its reliability for precise radiotherapy treatments.